The Impact of ESG Factors on Investment Decisions: Exploring the Interplay between Sustainability Reporting, Corporate Governance, and Financial Performance - Paranita, Ekayana Sangkasari; Ramadian, Afzil; Wijaya, Erric; Nursanti, Tinjung Desy; Judijanto, Loso (Journal of Ecohumanism, 2025)
ESG (Environmental, Social, and Governance) factors are increasingly a concern in investment decision-making, especially related to their role in influencing financial performance, sustainability reporting, and corporate governance. With a mixed method approach, this study combines quantitative and qualitative analysis to explore the relationship between these variables comprehensively. Quantitative analysis uses data from companies’ annual reports, ESG scores published by rating agencies, as well as financial data from companies listed on the stock exchange. The results of regression analysis and Structural Equation Modeling (SEM) show that ESG significantly affects financial performance, with corporate governance as a mediator that strengthens this relationship. In addition, sustainability reporting has been shown to increase investor confidence through increased transparency. On the qualitative side, in-depth interviews with investment managers and financial analysts provide insight that while ESG is considered important in investment decision-making, there are challenges in its implementation, including the diversity of reporting standards and long-term impact measurement. These findings underscore the importance of integrating ESG factors in investment strategies to create long-term value while supporting sustainability. The main recommendations are the harmonization of sustainability reporting standards and the strengthening of corporate governance to support the wider adoption of ESG-based investments.